Features and driving factors of microbial metabolic limitation in mountain ecosystems in arid areas: A case study on the Helan Mountains, Northwest China - Pang, Danbo; Liu, Bo; Wu, Mengyao; Li, Xuebin; Hu, Yang; Ma, Jinpeng; Zhao, Wenzhi; Chen, Lin (Frontiers in Forests and Global Change, 2022)
Understanding the limitations of soil microbial resources in mountain ecosystems is crucial to understand microbial functions and processes. Although the distribution pattern of soil microorganisms in mountain ecosystems has been widely studied, the role of soil microorganisms in biogeochemical cycles along elevation gradients in mountain ecosystems in arid regions is less understood. In this study, soil physicochemical properties, soil microbial community structure, extracellular enzymatic activities, ecoenzymatic stoichiometry, microbial metabolism, and their relationships were analyzed along an elevational gradient from 1,300 to 2,500 m under different vegetation types in the Helan Mountains, northwest China. Overall, the total microbial biomass and its components did not vary significantly among different elevations. The GP: GN (gram-positive: gram-negative bacteria) ratios at low elevations was higher than those the mid and high elevations, indicating that oligotrophic bacteria are enriched at low elevations. The five extracellular enzymes differed significantly among the different elevational gradient, the levels of carbon (C)- and nitrogen (N)-acquiring enzymes first increased and then decreased with increasing elevations. Ecoenzymatic stoichiometry indicated that microbial growth in the Helan Mountains limited by C and phosphorus (P) is more significantly at higher and medium elevations. Soil physicochemical characteristics, microbial community composition, and ecoenzymatic activities accounted for 43.94% of the microbial C restriction and 22.21% of the microbial P restriction. Overall, our results have provided valuable insights into changes in soil microbial metabolism along an elevational gradient in arid mountain ecosystems.